The impact of family background on educational attainment in Dutch birth cohorts 1966-1995 - Tilbe Atav; Cornelius A. Rietveld; Hans Van Kippersluis (Tinbergen Institute, 2023)
We analyse the evolving impact of family background on educational attainment using administrative data on 2,417,460 individuals from 1,341,403 families born in the Netherlands between 1966 and 1995. Comparisons between parents and their children reveal intergenerational elasticities between 0.15-0.18, translating into a 1.8-2.2 month increase in the educational attainment of the child associated with a oneyear increase in the educational attainment of the parent. Correlations between regular siblings explain 33 percent of the variance in educational attainment between individuals, with parental education accounting for approximately 75 percent of this share, suggesting that only around one-fourth of the variance is explained by factors that do not correlate with parental education. Strikingly, despite pervasive changes in the distribution of educational attainment over time, the share of the variance attributable to factors shared by siblings remains fairly stable at around 0.34 in the birth cohorts analysed. The intergenerational elasticity and intergenerational correlation also appear to be roughly stable across cohorts. Despite a reduction in overall education inequality, we conclude that family background has remained equally important for educational attainment in the analysed generations, although it appears to vary systematically by region of birth.
Keywords: D10; I24; J10; J62; 330; Relative correlations; intergenerational mobility; educational attainment